World War II in Finland, War Reparations, and the Sámi: The Side Effects of the war in Finland - Erickson, Patrick (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2024)
World War II was a time of chaos and upheaval across the globe, and Scandinavia was no exception. The war in Scandinavia had a significant impact on the Sámi, the indigenous people of Scandinavia. Sámi lands witnessed warfare, occupation, and destruction throughout the war. Sámi suffered greatly as they were forced from their homelands, forced into armed combat, and came home to lands ravaged by war. Because of accessibility, language barriers, and marginalization, little is written of the Sámi’s plight. Recent literature, has begun to focus on the Sámi during this time, and the present paper builds on their work. I examine these publishings and connect the dots of history through this time of chaos, illustrating that the Sámi suffered immensely and that their culture was permanently altered due to World War II.